Nurses’ care and management actions in emergency trauma cases - Azevedo, Ana Lídia Azevedo De Castro Sajioro; Scarparo, Ariane Fazzolo; Chaves, Lucieli Dias Pedreschi (Investigación y Educación en Enfermería, 2013)
<!-- [if gte mso 9]> <![endif]--> Objective. To analyze the nurse’s care and management actions in an emergency trauma hospital unit. Methodology. A qualitative, exploratory-descriptive multiple case study was undertaken in an emergency trauma unit in a public teaching hospital in a town in the state of São Paulo, Brazil. The data was collected through participant observation and semi-structured interviews with the nurses. Results. It was observed that the dimensions of care and management are interwoven in the nurse’s practice, which, based in the service users’ heath needs, uses specific knowledge referent to the prediction and provision of human and material resources and to actions articulating the team, to organize and guarantee the care, so as to offer integral care. Conclusion. The practice of the nurse in an emergency trauma service is close to the perspective of care management, articulating the work’s care and management dimensions. <!-- [if gte mso 9]> Normal 0 21 false false false ES-CO X-NONE X-NONE <![endif]--><!-- [if gte mso 9]> <![endif]--><!-- [if gte mso 10]> <![endif]-->